A new species of Hemerobiella Kimmins (Neuroptera, Hemerobiidae) from Venezuela with notes on the genus - Sosa, Francisco; Lara, Rogéria I. R.; Martins, Caleb C. (Zootaxa, 2015)
Hemerobiella periotoi Sosa & Lara sp. nov. is described from Venezuela. The new species was collected at the edges of a mature cloud forest in Lara state. This is the third species known in Hemerobiella Kimmins, and the second recorded from Venezuela. Additionally, new Venezuelan records and illustrations of H. oswaldi Monserrat, as well as, a key to Hemerobiella species are provided.